Clinical implications of using adrenocorticotropic hormone diagnostic cutoffs or reference intervals to diagnose pituitary pars intermedia dysfunction in mature horses - Remona Horn; Allison J. Stewart; Karen V. Jackson; Elizabeth L. Dryburgh; Carlos E. Medina‐Torres; François‐René Bertin (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Diagnosis of pituitary pars intermedia dysfunction (PPID) is problematic because of large variations in ACTH concentrations. Hypothesis/Objectives Compare the test characteristics of baseline and post–thyrotropin‐releasing hormone (TRH) stimulation plasma ACTH concentrations in horses using diagnostic cutoff values (DCOVs) and reference intervals (RIs) and determine the clinical consequences of using each method. Animals One hundred six mature horses: 72 control cases and 34 PPID cases. Methods Prospective case‐controlled study. Horses underwent monthly TRH stimulation tests. Diagnostic cutoff values were determined monthly by receiver operating characteristic curves using the Youden index. Reference intervals were determined monthly by a robust method. For each case age, sex and body condition score (BCS) were recorded. Results Baseline ACTH concentrations varied by month (P < .001) with significant “month × age” (P = .003), “month × sex” (P = .003), and “month × BCS” (P = .007) effects. Baseline ACTH concentrations were accurate to diagnose PPID (0.91 ± 0.06) with DCOVs increasing the test sensitivity (0.61 ± 0.21 to 0.87 ± 0.05, P = .002) and RI increasing test specificity (0.85 ± 0.12 to 0.98 ± 0.01, P = .01). Thyrotropin‐releasing hormone stimulation improved test accuracy (0.91 ± 0.06 to 0.97 ± 0.03, P = .004). Conclusions and Clinical Importance ACTH concentrations follow a circannual rhythm and vary with physiological factors. As using DCOVs increases the ability to detect mild cases and using RI decreases the risk of unnecessary treatments, ACTH concentrations should be interpreted within a specific clinical context. The TRH stimulation test improves the diagnosis of PPID.